5.4k views
0 votes
What is dy/dx if y = (x^2 + 2)^3 (x^3 + 3)^2

And please explain how you got your answer. I have no knowledge on how to get the answer AT ALL.

1 Answer

3 votes
We're given the following equation:

y=(x^2+2)^3(x^3+3)^2

In order to find
(dy)/(dx) we must differentiate both sides of the equation.

Lets start differentiating the left side (
y):

(d)/(dy) y=(1)dy=dy

The
(d)/(dy) simply servers to let us know we're differentiating whatever follows it (in this case
y) with respect to
y.

What we used to get the result is called the "power rule for differentiation" it states the following:

(d)/(ds) s^(n)=ns^(n-1)

In which
s is any variable (in the previous case
y) and
n is any constant (in the previous case this
n=1).

Now we'll differentiate the right side of the equation (
(x^2+2)^3(x^3+3)^2):

(d)/(dx)(x^2+2)^3(x^3+3)^2=[6x(x^2+2)^2(x^3+3)^2+6x^2(x^3+3)(x^2+2)^3]dx

What we did to differentiate the right side was, first, apply something called "product rule" for differentiation, it states the following:

(d)/(ds)[f(s)g(s)]= (d)/(ds)[f(s)]g(s)+(d)/(ds)[g(s)]f(s)

In which
f(s) and
g(s) are arbitrary functions of an arbitrary variable (
s) (in this case
f(s)=f(x)=(x^2+2)^3 and
g(s)=g(x)=(x^3+3)^2).

After that we applied something called "chain rule" for differentiation, which states the following:
if
h(s)=g(f(s)), then

(d)/(ds)[h(s)]= (d)/(ds)[g(f(s))] (d)/(ds)[f(s)]

Finally, the
dx we introduced as a factor after differentiating the right side (we also did it with the left side but with a
dy) is a consequence of the chain rule, it is always done.

Finally, equaling both differentiated sides of the equation we have:

dy=[6x(x^2+2)^2(x^3+3)^2+6x^2(x^3+3)(x^2+2)^3]dx


We solve for
(dy)/(dx), and the answer is:


(dy)/(dx) =6x(x^2+2)^2(x^3+3)^2+6x^2(x^3+3)(x^2+2)^3

User Kshepherd
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.